The development and prognosis of the world´s best performances in the women athletic throwing disciplines until 2016 - Brodani, J. (Acta Universitatis Matthiae Belii, Physical Education and Sport, 2013)
The aim of the work is to show the boundaries of the world´s best performances in throwing events of women in the years 2013 - 2016 in athletics. There has been established a question: "What performances can we expect in the 4-year brazil Olympic macrocycle in the athletic throwing events?" By working with the data and prognozing the values were used the methods os modeling the trend and extrapolation. The performances are prognosed with 90% probability. The overcome of the world´s best records of women in the years 2013 - 2016 are prognosed with 90% probabilty in all athletic throwing events. The choice of the regresive functions was based on the parametres of index determination, the significance of the slope of the regression line, the real value of the confidence interval, the statistical significance of the slope, the regression function, intuitive opinions of experts and specialists from athletic practice in Slovakia. We do not expect breaking the women best world records in shot put and in javelin, discus and hammer throw.